Caracterización de aislamientos nativos de hongos del género Cladorrhinum y su potencial como agentes antagonistas y promotores del crecimiento vegetal - Martín, Mara Edith (2019)
The genus Cladorrhinum (Phylum Ascomycota) includes soil saprotrophic fungi, among\nits representatives, C. foecundissimum, has been reported as a biocontrol agent and as a\ngrowth promoter as endophytes in cotton roots. Among their biotechnological skills, the\nsynthesis of endo-1,4-?-glucanases and cellobiohydrolases is reported.\nIn this thesis a polyphasic study of the genus Cladorrhinum spp., Including native isolates\nfrom Argentina, was proposed. The study was addressed by analyzing the role of these strains\nin the promotion of plant growth, as a biocontrol agent and their ability to synthesize enzymes\nof biotechnological importance, as well as their bioprospection at the genomic level. In order\nto select some of these strains with potential as biofungicides and biofertilizers, it will be\ndeveloped in the laboratory and in the culture chamber, analyzing the aspects related to their\nphysiology and their biotechnological applications.\nIt was found that the species C. samala surpassed C. foecundissimum in the activities\nreported for this species. The high intra-specific variability found in native strains of\nCladorrhinum spp. It supports the importance of this type of studies and the conservation in\ngermplasm banks. In this way the fungal biodiversity of the soil is protected.